How many large camelids in the world? A synthetic analysis of the world camel demographic changes - B. Faye (Pastoralism, 2020)
Abstract At world level, the current official number of large camelids cannot be determined exactly (it is estimated to be more than 35 million heads), and the role of camels in the livestock economy is highly variable. The only reliable statistics are provided by FAO since 1961. According to these data, five different patterns of demographic changes have been observed. In countries marked by a regular or drastic decline of their camelid population, a tendency to re-increase has been in force since the beginning of the century, except in India. Generally, countries marked by a sharp recent increase in their large camelid population have implemented a census and readjusted their data. Many inconsistencies occur in available data, most notably cases arising from changes occurring in state status (for example secession of Eritrea, Soviet Union collapse). Moreover, large camelid stocks in Australia, in countries of new camel establishment (Western countries) and those related to the expansion of camel farming, notably in Africa, are not recorded in the international database. In addition, there is no distinction between dromedary and Bactrian data. The present large camelid population in the world is probably more than 40 million and could reach 60 million after 25 years from now if the current demographic trend is maintained.